Photoconductive Properties of Brush Plated Copper Indium Gallium Selenide Films. (31st October 2013) - Subiramaniyam, N. P.; Thirunavukkarasu, P.; Murali, K. R.
Abstract : Copper indium gallium selenide (CIGS) films were deposited for the first time by the brush electrodeposition technique. X-ray diffraction studies indicated the formation of single phase chalcopyrite CIGS. Lattice parameters, dislocation density, and strain were calculated. Band gap of the films increased from 1.12 eV to 1.63 eV as the gallium concentration increased. Room temperature transport parameters of the films, namely, resistivity increased from 0.10 ohm cm to 12 ohm cm, mobility decreased from 125 cm 2 V −1 s −1 to 20.9 cm 2 V −1 s −1, and carrier concentration decreased from 4.99 × 10 17 cm −3 to 2.49 × 10 16 cm −3 as the gallium concentration increased. Photosensitivity of the films increased linearly with intensity of illumination and with increase of applied voltage.